KONSEP ILMU DALAM PENDIDIKAN ISLAM: RELEVANSI TERHADAP MATERI PEMBELAJARAN KONTEMPORER - Noer, Mohammad Fahrudi (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2024)
Abstract This article examines the concept of knowledge within the perspective of Islamic education and its relevance to the development of contemporary learning materials. In Islamic educational thought, knowledge is considered a means to draw closer to Allah SWT, to cultivate noble character, and to build a civilization based on divine values. However, in the current educational context, learning systems tend to focus on technical and instrumental aspects, while separating religious knowledge from secular sciences. This division has led to the erosion of spiritual and ethical values in the learning process. This study employs a qualitative approach in the form of library research, using content analysis of primary sources relevant to Islamic epistemology and contemporary educational challenges. The findings indicate that integrating Islamic scientific values into the curriculum can serve as a solution to modern educational issues. Emphasis on values such as adab (ethics), tawhid (monotheism), and hikmah (wisdom) in the learning process is essential to restoring the true essence of Islamic education. Thus, Islamic education is expected to produce learners who are not only intellectually competent but also spiritually strong and morally upright.